Desain Motion Comic Tentang Bahaya Kecanduan Game Online Bagi Siswa Sekolah Dasar - Farhan Hanif Ramadhan Sugiyanto; Yudi Wibowo; Ahmad Khoirul Anwar (Universitas Sahid Surakarta, 2026)
The development of digital technology has made elementary school students increasingly familiar with online games, which are now part of their daily activities. Excessive online gaming has the potential to lead to addiction and negatively impact concentration, time management, and academic performance. Elementary school students' understanding of the dangers of online game addiction remains low, and educational media that are not yet appropriate to their characteristics and interests are lacking. This project aims to create a visual communication medium in the form of a motion comic about the dangers of online game addiction for elementary school students. The design method used is design thinking, which includes the stages of empathize, define, ideate, prototype, and test. Data collection techniques used literature studies and questionnaires. The resulting design is a motion comic titled